A Path Loss Model for Non-Line-of-Sight Ultraviolet Multiple Scattering Channels - Sadler BrianM; Ding Haipeng; Xu Zhengyuan (EURASIP Journal on Wireless Communications and Networking, 2010)
An ultraviolet (UV) signal transmission undergoes rich scattering and strong absorption by atmospheric particulates. We develop a path loss model for a Non-Line-of-Sight (NLOS) link. The model is built upon probability theory governing random migration of photons in free space, undergoing scattering, in terms of angular direction and distance. The model analytically captures the contributions of different scattering orders. Thus it relaxes the assumptions of single scattering theory and provides more realistic results. This allows us to assess the importance of high-order scattering, such as in a thick atmosphere environment, where short range NLOS UV communication is enhanced by hazy or foggy weather. By simulation, it is shown that the model coincides with a previously developed Monte Carlo model. Additional numerical examples are presented to demonstrate the effects of link geometry and atmospheric conditions. The results indicate the inherent tradeoffs in beamwidth, pointing angles, range, absorption, and scattering and so are valuable for NLOS communication system design.